ACTION LINES OF THE OUT-OF-FAMILY CARE SUPPORT CENTER FOR SUPPORTING FOSTER FAMILIES - Gorina, Maritana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Latvian foster families has an important role to play in enabling children in the family environment and learning to live there. Much of the foster parents in daily life is faced with a variety of difficulties, for example by reference to the national rights of Children of Defence Inspection Study (2016) often, municipalities are not interested in financing childcare relationships relied care and in some of the following delays  of the assistance, the payment of benefits, allocation to foster families, often local authorities do not give any additional assistance in particular in the event of a number of children or children with health problems, often People who want to get foster parents status are problematic to get to the training site. In accordance with article 36.1 of the Children's Rights Protection Act, the third and fourth subparagraphs, which enter into force on 1 July 2018, provide for the establishment of relationships relied care support centers. As the idea of building a relationship relied, care support Center is new, it is important to highlight its scope. According to the method of the survey, a entrusted of difficulties has been identified in the daily analysis and evaluation of the results of the out-of-family care center action plan.